(untitled) (Universal International Scientific Journal, 2026)
This article examines the relationship between musical culture and Uzbek traditional values ​​in the upbringing of young people. It examines the role of moral, aesthetic and social factors of such types of music as maqom, kuy-kashyk, ashulalar, folk songs in the formation of educational effects in the minds of young people. It shows that traditional values ​​​​(readiness to address, hospitality, appreciation of labor pride, and meetings, family and local harmony) are passed down from generation to generation through music, demonstrating examples of recent history and culture.